Distribution of Hordelymus europaeus (L.) Jess. ex Harz in forest communities of the Beskid Mały Mountains - Barć, Alicja; Brzustewicz, Małgorzata (Biodiversity: Research and Conservation, 2006)
The paper presents original and literature data concerning the current distribution of the rare grass Hordelymus europaeus (L.) Jess. ex Harz in the Beskid Mały Mts. (southern Poland). This study confirms the persistence of H. europaeus in Zwalisko (ATPOL DF96). Hitherto, resources of this species have been studied in the eastern part of the range and Suszyce was distinguished as the area of its concentration. New localities on slopes of Suszyce do not change the distribution pattern of the species in the ATPOL 10 km x 10 km grid, because these are in the same square as Zwalisko. Despite that, they should be treated as separate ones. Moreover, extreme localities within Suszyce could also be treated as separate ones, as they represent different squares in the ATPOL subgrid (2 km x 2 km).